Evaluation of men’s knowledge, attitudes, and performance toward Prostate Cancer in the Urology Clinic of Imam Khomeini Hospital, Urmia, Iran - Tayyebi Azar, Ali; Farshid, Saman; Masoudi, Sima; Yuzbashi, Simin (Archives of Men’s Health, 2022)
Introduction: Prostate cancer is the second most common cancer after lung cancer worldwide. In 2018, there were 1276106 new cases and 3.8% (358989 cases) of the population who died of this cancer were men. (What do you mean? All were men because we are talking about prostate cancer, but do you mean the mortality rate?) We aimed to evaluate men’s knowledge, attitudes, and performance toward prostate cancer. Materials and Methods: A descriptive analysis was done on 385 men in the urology clinic of Imam Khomeini Hospital. Men aged at least 40 with no history of prostate cancer were included in this survey. The researchers made a questionnaire including two parts: the first part comprised information about knowledge, attitudes, performance, and the second part consisted of demographics. The men’s function was divided into two groups according to performing the PSA test: the good function group (PSA tests were done) and the weak function group (PSA tests were not done). Data analyzed were analyzed using SPSS software, version 20. Results: The mean±SD age of the men was 63.9±8.9 years and 56.6% of them were city dwellers. 22.7% had a university degree. Most (38.5%) were Self-employed and most (76.3%) had no family history of prostate cancer. Most participants answered the general questions about prostate cancer, but they did not have suitable and reliable information about related risk factors, diet, and sexual activity. ‌ Conclusion: Considering the positive effect of people’s knowledge on their attitude and their attitude on their performance, by holding training classes and education for people at risk their attitude and ultimately their performance towards prostate cancer prevention would be improved.